Bactérias potencialmente resistentes a antibióticos, desinfetantes e radiação ultravioleta, isoladas de esgoto hospitalar e esgoto sanitário - Ferreira, João Cairo (2015)
The use of water and its posterior release into hydric bodies can be a possible factor of dissemination of microorganisms potentially pathogenic and/or resistant. The presence of these organisms in treated or untreated water may represent considerable threat to the general population’s health and the environment. In Brazil, according to current legislation, health assistance establishments can direct its effluents to the sewage treatment and collection network together with domestic sewage. Taking into consideration the survival of pathogenic microorganisms released in hospital sewage as well as its permanence after treatment processes, this study realized the quantification, isolation and identification of opportunistic environmental and/or fecal-oral bacteria (Acinetobacter spp., Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa e Staphylococcus aureus), present in hospital sewage and in sewage treatment station entry and exit –ETE, and studied the sensibility of these isolated towards antimicrobials (antibiotics and disinfectants) and exposure to UV (Ultraviolet Radiation). Sewage samples were collected during a period of 8 months (from May to December 2013) to analyze their chemical-physical parameters (COD, Series of Solids, pH, Nitrogen Ammonia, Turbidity) and to carry out microbiological analyses (Isolation, quantification and identification) and sensibility tests to the most used antibiotics and disinfectants by Brazilian hospitals and in contact with UV radiation. The presence of all the species/ genus, which were the focus of this study, was detected in all collection points plus their resistance to tested antibiotics and proposed treatments. One of the low efficiency factors for the treatments were the high amount of suspended solids dispersed in the effluent and the increasing multi-resistance emergency to antibiogram tests. These factors have created the need for greater control by the scientific community and the general population in regards to the impact of the presence of these bacteria in sewages and later in hydric bodies, its ecosystem and public health.